2017
DOI: 10.1111/jfpp.13516
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antioxidant activity of essential oils in Origanum vulgare subsp. gracile at different phenological stages and plant parts

Abstract: Origanum vulgare, a popular flavoring herb, is valued for several biological properties. The present study focused on the chemical composition and antioxidant activity of the essential oils of Origanum vulgare subsp. gracile in different plant parts and at different phenological stages. Qualitative and quantitative analyses of the essential oil identified 41 constituents that varied with plant age and organ. The phenolic monoterpenoid carvacrol (18.1–79.2%) was predominant in all the essential oil samples. Oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 41 publications
1
27
1
Order By: Relevance
“…Furthermore, they possess various biological activities whose potentials have been revealed by several scientific studies exposed to the public 4,5 ; indeed some species are available in almost all public markets. The genus Origanum belongs to the family of Lamiaceae, called "Oregano" in English.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they possess various biological activities whose potentials have been revealed by several scientific studies exposed to the public 4,5 ; indeed some species are available in almost all public markets. The genus Origanum belongs to the family of Lamiaceae, called "Oregano" in English.…”
Section: Introductionmentioning
confidence: 99%
“…Rubbing of whole Greek oregano herb was performed after drying, on sieves with a mesh diameter of 4–5 mm. In this process, stems (according to Morshedloo et al ., having the lowest percentage of essential oil because of the low density of glandular trichomes) were removed and raw material was crushed. In our experiment, the share of rubbed herb in the whole Greek oregano herb was highest in the early developmental phases (accounting for about 70%), probably owing to the smaller share of stems in the young Greek oregano plants.…”
Section: Resultsmentioning
confidence: 99%
“…In the available literature, there is no detailed information on the most appropriate date for harvesting Greek oregano's raw material. Works with Greek oregano and other essential oil‐bearing plants have demonstrated that essential oil production can differ with the phenological growth; moreover, variation in essential oil chemical composition may occur Therefore it is very important to specify more precisely when the raw material should be harvested in order to ensure, on the one hand, the highest possible quality and, on the other hand, the highest possible yields of Greek oregano.…”
Section: Introductionmentioning
confidence: 99%
“…determined the greatest amounts of essential oil in Origanum vulgare subsp. gracile during flowering stage compared to the early and late vegetative stages . The essential oil composition of plants is very diverse, even the same species possess a certain amount of chemotypes depending on the predominant compound .…”
Section: Discussionmentioning
confidence: 99%
“…gracile during flowering stage compared to the early and late vegetative stages. [45] The essential oil composition of plants is very diverse, even the same species possess a certain amount of chemotypes depending on the predominant compound. [2] We have determined that b-phellandrene as the prevailing compound in the above-ground parts of H. pyrenaicum plants.…”
Section: Discussionmentioning
confidence: 99%